Observer‐aided resilient hybrid fractional‐order controller for frequency regulation of hybrid power system. (12th July 2021) - Guha, Dipayan; Roy, Provas Kumar; Banerjee, Subrata
Summary: This article maidenly presents a resilient hybrid fractional‐order controller (hy‐FOC) comprised of fractional‐order proportional‐integral‐derivative (FOPID) controller and fractional‐order sliding mode controller (FOSMC) for frequency regulation of an islanded hybrid power system (HPS) integrated with a doubly‐fed induction generator (DFIG)‐driven wind power generator. The slime mould algorithm is applied to obtain near‐optimum gains of the hy‐FOC via the minimization of an integral error criterion. Moreover, a Luenberger disturbance observer (Dob) is designed to estimate uncertain plant disturbances and incorporate estimated output into the control law to alleviate chattering in the output of sliding mode controller (SMC). The acceptability and superiority of the proposed hy‐FOC are established by performing an extensive comparative study with the results of PI‐derivative (PID), SMC, FOPID, and FOSMC under diverse operating conditions (model uncertainties and uncertain external disturbances). The simulation results are presented and discussed to authenticate proficiency of the proposed resilient control methodology over its other integral‐order and fractional‐order counterparts. Governor dead‐band and generation rate constraint (thermal unit) as a provenance of physical limitations are also considered in the model to show the proposed controller's effectiveness for handling the practical challenges. Lastly, the sensitivity and robustness of the proposed approach have been affirmed by varying system parameters between ±25% of nominal settings. Abstract : A, Pole‐zero model of islanded HPS, B, model of DFIG driven WTG system Proposed control strategy for regulation of HPS frequency